2xx-5x-12
2*-12=-24
-24=-8*3
-8+3=-5
2xx-8x+3x-12
2x(x-4)+3(x-4)
(2x+3)(x-4)
Chat with our AI personalities
2x2 - 5x + 12 does not factor. 2x2 - 5x - 12 factors into (2x + 3)(x - 4) 2x2 + 5x - 12 factors into (2x - 3)(x + 4)
-((2x + 7)(x - 6))
2x2 - 72 would be factored into (2x - 12)(x + 6) or (2x + 12)(x - 6) To double check, multiply each pair: (2x - 12)(x + 6) = 2x2 + 12x - 12x - 72 = 2x2 - 72 (2x + 12)(x - 6) = 2x2 - 12x + 12 x - 72 = 2x2 - 72
4x2 - 2x - 12= 2x2 - x - 6= 2x2 - 4x + 3x - 6= 2x(x - 2) + 3(x - 2)= (x - 2)(2x + 3)
you can do 5 12 times